A recurrent de novo FAM111A mutation causes kenny–caffey syndrome type 2. (April 2014) - Isojima, Tsuyoshi; Doi, Koichiro; Mitsui, Jun; Oda, Yoichiro; Tokuhiro, Etsuro; Yasoda, Akihiro; Yorifuji, Tohru; Horikawa, Reiko; Yoshimura, Jun; Ishiura, Hiroyuki; Morishita, Shinichi; Tsuji, Shoji; et al.
ABSTRACT Kenny–Caffey syndrome (KCS) is a rare dysmorphologic syndrome characterized by proportionate short stature, cortical thickening and medullary stenosis of tubular bones, delayed closure of anterior fontanelle, eye abnormalities, and hypoparathyroidism. The autosomal dominant form of KCS (KCS type 2 [KCS2]) is distinguished from the autosomal recessive form of KCS (KCS type 1 [KCS1]), which is caused by mutations of the tubulin‐folding cofactor E (TBCE) gene, by the absence of mental retardation. In this study, we recruited four unrelated Japanese patients with typical sporadic KCS2, and performed exome sequencing in three patients and their parents to elucidate the molecular basis of KCS2. The possible candidate genes were explored by a de novo mutation detection method. A single gene, FAM111A (NM_001142519.1), was shared among three families. An identical missense mutation, R569H, was heterozygously detected in all three patients but not in the unaffected family members. This mutation was also found in an additional unrelated patient. These findings are in accordance with those of a recent independent report by a Swiss group that KCS2 is caused by a de novo mutation of FAM111A, and R569H is a hot spot mutation for KCS2. Although the function of FAM111A is not known, this study would provide evidence that FAM111A is a key molecule for normal bone development, height gain, and parathyroid hormone development and/or regulation. © 2014 American Society for Bone and Mineral Research.